A antiga linha férrea de Goiânia. De símbolo da modernidade à obsolescência - Brandão, Simone Buiate (2017)
This research is an agony verbalization for what has been left to oblivion in Goiania’s landscape, the ancient railroad of Goiás Railway. It used to be the modernization symbol of Goiás State and of the city construction, it was built in the 1950’s, from the extension of a railroad branch originated in the trunk line Araguari – Anápolis. The railway used to cross the whole state, to the north of the country, with the goal to reach the new capital of sertão, Brazil’s very deep country side, departing from Leopoldo de Bulhões and getting into the city perimeter up to Campinas, the oldest district in Goiânia. However, the golden years of the railway were too short, the late arrival of the trails coincided with the highways’ fast progress in the country, while the railways suffered many reflexes from the lack of investments and serious financial problems, besides the undercarriage’s obsolescence. Thus, a dream coming true became a nightmare, resulting on the partial deactivation process of the rail branch. This had boosted the increase of irregular neighboring areas occupations, the abandonment of spaces and the immediate removal of some trails. However, remains of a railway area were left, such as the stations, few residences and trails which unveil a past. This past is present like a ghost, who still walks by the city almost unseen by great majority of the population. Having this in mind, the aim of this study is to elaborate a story in order to understand and analyze the landscape that has been transformed along the years with the insertion of this modernity instrument in the urban tissue of Goiânia. The methodological procedures were based on bibliographic researches, documents analysis, on printed and electronic material from private and public institutions, on field and mapping services. This work helped us to understand how the railway has interfered in the formation and transformation of the space along the years until today, unveiling four distinct axes: the superposition axe, a path where nowadays one can find the Leste-Oeste Avenue, which has replaced the trails; the destruction axe, which comprises the Trabalhador Square, where one can find the Railway Station that suffers constant reuse try-outs, but nowadays is abandoned; the crossties’ cemetery, a path full of railway remains; and, finally, the resistance axe, the only path where the train still operates. In this way, this study tries to fulfil a gap in Goiás Railway’s history that has not been registered yet. At the same time, it establishes a base for new stories that could deeply explore each axe identified.